Penerapan Arsitektur Berwawasan Lingkungan pada Rancangan Sentra Bordir di Kabupaten Pasuruan Jawa Timur - Rizal, Ahmad Fahmi Fatchur; Widjajanti, Wiwik Widyo; Salisnanda, Randy Pratama (Institut Teknologi Adhi Tama Surabaya, 2021)
Abstract. Pasuruan is famous for top products of embroidery that are resulted by Small and Medium Industries. The production of embroidery has widely spread in all districts of Pasuruan Regency, particularly in Bangil District. Embroidery refers to ornaments attached on the clothes or other materials made by needle and thread. It also belongs to one of ornamental craft varieties (clothes accessory) which focuses on the beauty and competition of thread colors on the clothes as the media supported by a set of sewing kits (embroidery sewing machine) or computerized-embroidery sewing machine. The ornament of embroidery can use not only thread but also other materials such as metal pieces, pearls, beads, bird feather, and sequins. Planning and designing Embroider Centre are intended for providing a place of production and marketing upon craft products as well as supporting other activities such as the centre of promotion, information, and cultural education, which later on, it can become a tourism potential which is beneficial for developing the local and economy of Pasuruan society. The use of sustainable architecture theme in designing this building is expected to present a certain character or identity of facility and gallery. Besides, sustainable architecture also emphasizes on the surrounding environment such as conserving energy, working climate, respect for site, respect for user, and holistic. The designing process of building architecture was carried out through a series of stages beginning from project identification, precedent study, design program, design concept, and design development.Keywords: Embroidery, Embroidery Centre, Sustainable Architecture Abstrak. Pasuruan ini memiliki produk IKM yang menjadi produk unggulan yaitu bordir. Produksi bordir tersebar luas di seluruh Kabupaten Pasuruan, terutama di Kecamatan Bangil. Bordir merupakan hiasan diatas kain atau bahan- bahan lain dengan jarum jahit dan benang. Bordir juga bisa didefinisikan sebagai salah satu kerajinan ragam hias (untuk aksesoris busana) yang menitik beratkan pada keindahan dan kompetisi warna benang pada medium berbagai kain dengan alat bantu seperangkat mesin jahit (mesin jahit bordir) atau mesin jahit bordir komputer. Selain benang, hiasan untuk sulaman atau bordir dapat menggunakan bahan-bahan seperti potongan logam, mutiara, manik-manik, bulu burung, dan payet. Perencanaan dan Perancangan Sentra Bordir ini memiliki tujuan yaitu sebagai tempat produksi dan pemasaran hasil kerajinan serta adanya aktivitas lain diantaranya adalah pusat promosi, informasi, budaya edukasi sehingga nantinya mampu menjadi potensi wisata yang dapat memberi manfaat bagi pengembangan daerah dan ekonomi masyarakat diKabupaten Pasuruan. Penggunaan tema Arsitektur Berwawasan Lingkungan dalam perancangan bangunan ini diharapkan dapat menampilkan suatu karakter atau identitas dari fasilitas dan galeri itu sendiri, tidak hanya itu Arsitektur Berwawasan Lingkungan juga mengedepankan lingkungan sekitarnya meliputi conserving energy, working climate, respect for site, respect for user, holistic. Perancangan arsitektur bangunan dilakukan melalui serangkaian tahapan mulai dari identifikasi proyek, studi preseden, program rancangan, konsep hingga pengembangan rancangan.Kata Kunci: Bordir, Sentra Bordir, Arsitektur Berwawasan Lingkungan